Recurrent pregnancy loss and frequency of eight antiphospholipid antibodies and genetic thrombophilic factors in Czech women - Šubrt, Ivan; Ulčová-Gallová, Zdenka; Bibková, Katarína; Mičanová, Zdeňka; Hejnalová, Markéta; Černá, Monika; Hradecký, Libor; Novotný, Zdeněk (American journal of reproductive immunology, 2008)
PROBLEM: The aim of this study was to investigate frequencies of eight antiphospholipid antibodies (aPLs) in serum, four genetic thrombophilic factors and their mutual relation in 206 patients with repeated pregnancy loss (RPL). METHOD OF STUDY: Enzyme-linked immunosorbent assay was used for detection of aPLs against ph-serine, ph-ethanolamine, ph-inositol, DL-glycerol, phosphatidic acid, anti-annexin V, cardiolipin, and beta2-GPI. FV 1691G>A (Leiden mutation), FII 20210G>A mutation, MTHFR 677C>T and MTHFR 1298A>C variant genotypes were determined using a melting curve analysis of the PCR amplification product detected by the fluorescence resonance energy transfer. Genotypic distribution and allelic frequencies were calculated. Correlation between aPLs and thrombophilic factors was tested by chi-square and Fisher exact test. RESULTS: Our results show significantly increased prevalence of aPLs against ph-inositol (17-19.6% dependent on number of spontaneous miscarriages) and against ph-serine (18-25%). aPLs in IgG prevail. In 96% of the studied group, at least one risk factor was found (either aPLs positivity or thrombophilic factor). Both aPLs and thrombophilic factors were present in 43%. In the group of women with three or more RPLs, strong positive correlation of aPLs positivity and thrombophilic risk factors was observed. CONCLUSION: Antiphospholipide antibodies and genetic thrombophilic factors are important risk factors in the pathogenesis of RPL. Both autoantibodies against various kinds of phospholipides and genetic thrombophilic factors must be studied together in diagnosis of RPL for appropriate treatment
Keywords: Czech Republic; Humans; Pregnancy Outcome; kauzalita; lidé; trombofilie; habituální potrat; těhotenství; Abortion, Habitual; DNA sondy; Thrombophilia; frekvence genu; Causality; antifosfolipidové protilátky; mutace; Female; lidé středního věku; Pregnancy; Mutation; rizikové faktory; Enzyme-Linked Immunosorbent Assay; genotyp; Gene Frequency; průřezové studie; Antibodies, Antiphospholipid; Risk Factors; výsledek těhotenství; Adult; dospělí; Genotype; DNA Probes; ELISA; Česká republika; Cross-Sectional Studies; Middle Aged; ženské pohlaví